Decoding ultramarathon: muscle damage as the main impediment to performance - Tiller, N. B.; Millet, G. Y. (Sports Medicine, 2025)
The biological determinants of performance have been well described for running races up to and including the marathon (42.2 km). Ultramarathon is more complex. Events range from 50 to 5000 km in single or multiple stages, are contested in various environments and terrains, and force athletes to contend with diverse performance-limiting issues such as fueling, hydrating, gastrointestinal distress, muscle damage, and sleep deprivation. Ultramarathons are not simply "long marathons." Nevertheless, scientific developments over the past decade have inched us toward a more complete picture of the psychophysiological factors underpinning performance. In this Current Opinion, we argue that muscle damage and associated fatigue is the main impediment to performance in long ultramarathons; more performance-limiting than aerobic capacity, running economy, or gastrointestinal distress. To assess an athlete`s tolerance to ultramarathon-specific muscle damage and fatigue, we propose a lab-based protocol comprising downhill running with pre- to post-exercise measures of muscle contractile function following electrical or magnetic stimulation of the quadriceps muscles or their central nerves, muscle damage biomarkers (e.g., creatine kinase, lactate dehydrogenase, and myoglobin), and muscle morphology via imaging techniques. We close by offering training and racing advice on mitigating the deleterious effects of muscle damage. The twofold aims of this paper are (i) to enable athletes and their teams to better prepare for races and (ii) to help medical personnel identify the physiological milieu most likely to afflict the ultrarunner.